The study of paraoxonase (PON1) activity, oxidized low-density lipoprotein (Ox-LDL) and augmentation index (A1x) among healthy population /: - Mohd Hakam bin Nazir (Kulliyyah of Medicine, International Islamic University Malaysia, 2014)
Arterial stiffness is a hall mark of aging and is also associated with a number of cardiovascular risk factors such as hypercholesterolemia, hypertension, diabetes mellitus and smoking.Augmentation index (AIx), a surrogate measure of arterial stiffness, has been increasingly used for its simple and non-invasive technique.The goal of this research is to study the association between paraoxonase (PON1), oxidized low-density lipoprotein (Ox-LDL) and augmentation index (AIx) in the healthy population in Chengal Lempong village. Apparently healthy subjects (n=85) of age (>18 years) were randomly selected. PON1 activities towards substrates paraoxon, phenylacetate and diazoxon and lipid profile were analysed by standard methods. Measurement of oxidized low-density lipoprotein (Ox-LDL) was done by using Mercodia Ox-LDL ELISA. The augmentation index (AIx) which reflects the arterial stiffness was determined by using non-invasive applanation tonometry, SphygmoCor device (At Cor Medical, Australia). The results showed that mean age of the subjects were 40±8 years with male and female distribution were 38(45%) and 47(55%) respectively. 35.3% and 41.2% of the subjects were obese and overweight. As much as 62(73%) and 23(27%) of them were nonsmokers and smokers. PON1 activities towards paraoxon, diazoxon and phenylacetate were not statistically correlated with augmentation index. Although there was no statistically significant correlation between augmentation index and Ox-LDL, augmentation index was increased with increased Ox-LDL suggesting that oxidative modification of LDL may play a role in the alteration of arterial wall elastic properties. Paraoxonase was not significantly associated with Ox-LDL.The present study demonstrates for the first time in association between PON1, Ox-LDL and augmentation index among the population. Although this association did not reach statistical significant, augmentation index may be a useful marker of cardiovascular risk.